2020
DOI: 10.3390/app10186239
|View full text |Cite|
|
Sign up to set email alerts
|

Bone Healing and Regeneration Potential in Rabbit Cortical Defects Using an Innovative Bioceramic Bone Graft Substitute

Abstract: This study aimed to elucidate the local effect and micro-computed tomographic (μ-CT) assessment following bone implantation of an innovative bioceramic (α-calcium sulfate hemihydrate; α-CSH) on femur lateral condyle cortical bone of rabbit models. The innovative α-CSH bioceramic was synthesized through a green processing technology (microwave irradiation treatment). The bilateral implantation model was performed among 24 New Zealand White rabbits which were divided into three groups based on the type of fillin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 48 publications
1
0
0
Order By: Relevance
“…Group (CN) showed minimal amount of newly formed bone trabeculae dispersed in rich highly cellular granulation tissue. These findings were consistent with Ou et al, (47) who discovered that femoral defects in rabbit showed fibrous connective tissue with only a few bone trabeculae formed four weeks after surgery, and Santos et al, (48) reported the presence of granulation tissue only in the defect area with no signs of new bone formation in the negative control group 4 weeks post-operatively.…”
Section: Discussionsupporting
confidence: 89%
“…Group (CN) showed minimal amount of newly formed bone trabeculae dispersed in rich highly cellular granulation tissue. These findings were consistent with Ou et al, (47) who discovered that femoral defects in rabbit showed fibrous connective tissue with only a few bone trabeculae formed four weeks after surgery, and Santos et al, (48) reported the presence of granulation tissue only in the defect area with no signs of new bone formation in the negative control group 4 weeks post-operatively.…”
Section: Discussionsupporting
confidence: 89%